Emergent low-energy bound states in the two-orbital Hubbard model - Núñez Fernández, Yuriel (2018)
A repulsive Coulomb interaction between electrons in different orbitals in correlated materials can give rise to bound quasiparticle states. We study the nonhybridized two-orbital Hubbard model with intra- (inter)orbital interaction U(U12) and different bandwidths using an improved dynamical mean-field theory numerical technique which leads to reliable spectra on the real energy axis directly at zero temperature. We find that a finite density of states at the Fermi energy in one band is correlated with the emergence of well-defined quasiparticle states at excited energies Δ=U-U12 in the other band. These excitations are interband holon-doublon bound states. At the symmetric point U=U12, the quasiparticle peaks are located at the Fermi energy, leading to a simultaneous and continuous Mott transition settling a long-standing controversy.